Experimental Investigation on Characteristics of Evaporator Vaporization and Pressure Drops in an Organic Rankine Cycle (ORC). (August 2015) - Hu, Kaiyong; Zhu, Jialing; Li, Tailu; Lu, Xinli; Zhang, Wei
Abstract: In this paper, an experimental study on the heat transfer and pressure drop of R245fa in a brazed plate heat exchanger (BPHE) for organic Rankine cycle (ORC) was carried out. The effects in terms of heat flux, working fluid mass flux, heat source temperature, and super-heated degree at the outlet of the BPHE were investigated. Experiments were conducted for mass flow rate ranging from 120 to 180 kg/h with heat flux ranging from 11 to 14kw/m 2 . The current study indicated that the heat transfer coefficients show great sensitivity to heat flux and working fluid mass flow rate. However, the corresponding pressure drop increased with increasing the mass flow rate and heat flux. Therefore, work should be carefully done in evaporator design considering the equilibrium of economic and heat transfer efficiency.